2022
DOI: 10.1038/s41420-022-01106-1
|View full text |Cite
|
Sign up to set email alerts
|

Grb2 interacts with necrosome components and is involved in rasfonin-induced necroptosis

Abstract: The underlying mechanism by which growth factor receptor-bound protein 2 (Grb2) regulates necroptosis remains unexplored. In the present study, we found that rasfonin, a fungal natural product and an activator of necroptosis, enhanced Grb2 binding to receptor-interacting serine/threonine kinase 1 (RIP1), which plays a critical role in regulating programmed necrosis. Moreover, we observed that SQSTM/p62 (p62), a protein that can form necrosomes with RIP1, increased its interaction with Grb2 upon rasfonin challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…According to gene expression data, the death of treated HCT116 cells occurred through extrinsic apoptosis ( 63 ) mediated by the death receptors DR4 and DR5 encoded by the TNFRSF10A and TNFRSF10B genes, respectively. The overexpression of the GRB2 gene indicated that part of the HCT116 cells was engaged in necrosis/necroptosis ( 64 ), while the overexpression of ULK1 evidenced the occurrence of autophagy ( 65 ) at 24 h after radioisotope addition.…”
Section: Discussionmentioning
confidence: 99%
“…According to gene expression data, the death of treated HCT116 cells occurred through extrinsic apoptosis ( 63 ) mediated by the death receptors DR4 and DR5 encoded by the TNFRSF10A and TNFRSF10B genes, respectively. The overexpression of the GRB2 gene indicated that part of the HCT116 cells was engaged in necrosis/necroptosis ( 64 ), while the overexpression of ULK1 evidenced the occurrence of autophagy ( 65 ) at 24 h after radioisotope addition.…”
Section: Discussionmentioning
confidence: 99%